Microperimetry as an outcome measure in RPGR-associated retinitis pigmentosa clinical trials - Taylor, LJ; Josan, AS; Jolly, JK; MacLaren, RE (Association for Research in Vision and Ophthalmology, 2023)
Purpose: To explore which microperimetry sensitivity index (pointwise sensitivity, mean sensitivity, and volume sensitivity) is suitable as a microperimetry outcome measure in patients with X-linked RPGR-associated retinitis pigmentosa (RP). Methods: Microperimetry data from patients with RPGR-associated RP were collected and analyzed retrospectively. Fourteen participants completed triplicate microperimetry testing, across 2 consecutive days for the repeatability analyses. Longitudinal data was obtained from 13 participants who completed microperimetry testing at two separate visits. Results: The test–retest coefficients of repeatability (CoR) for pointwise sensitivity were ±9.5 dB and ±9.3 dB, in the right and left eyes, respectively. The mean sensitivity CoR for the right and left eyes was ±0.7 dB and ±1.3 dB. Volume sensitivity CoR was ±144.5 dB*deg2 and ±324.2 dB*deg2 for the right and left eyes, respectively. The mean sensitivities were positively skewed toward zero in those with a high number of nonseeing points (arbitrarily assigned to −1.0 dB) and just seen points (0.0 dB). Volume sensitivities were unaffected by the averaging effects of skewed data. Conclusions: Clinical trials should report population-specific test–retest variability to determine a clinically significant change. Pointwise sensitivity indices should be used with caution as outcome measures in clinical trials owing to high levels of test–retest variability. Global indices seem to be less prone to variability. Volume sensitivity indices seem to be superior for use in RPGR-associated RP clinical trials compared with mean sensitivity because they are unaffected by the averaging effects of highly skewed data. Translational Relevance: Careful selection of sensitivity indices (VA) is required when using microperimetry as a clinical trial outcome measure.